PERAN BRAND TRUST MEMEDIASI PENGARUH BRAND IMAGE TERHADAP BRAND LOYALTY - Putra, I Wayan Govinda Gotama Putra; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 8 No 7 (2019)DO - 10.24843/EJMUNUD.2019.v08.i07.p12, 2019)
This research was conducted with the aim of measuring and testing the effect of brand image on brand loyalty with brand trust as a mediator. One hundred badminton players using Shuttlecock Pastra were used as samples, the method used was purposive sampling. The study was conducted in Denpasar City and distributed questionnaires to prospective respondents as many as 100 people selected through a purposive sampling technique. Path analysis techniques and sobel tests are used to analyze data. After investigating, it was found that brand image variables had a positive and significant effect on brand trust variables, brand image variables had a positive and significant effect on brand loyalty variables, brand trust variables had a positive effect that was also significant for brand loyalty variables and brand trust variables were able to mediate the influence of brand image on brand loyalty shuttlecock Pastra. Keywords: brand image, shutllecock, brand trust, Pastra, brand loyalty